Akta Perdamaian Oleh Notaris Sebagai Mediator Alternatif Penyelesaian Sengketa Di Luar Pengadilan - Wijaya Natalia Panjaitan (Pattimura Legal Journal)
Introduction: Deed of Peace by a Notary is one of the authority by the Attributive for Notary. This is one of the notary's active roles to act to resolve disputes outside the court.